The crystal structure of 5,5′-diselanediyl-bis(2-hydroxybenzaldehyde), C14H10O4Se2 - Tingting Lin; Qiuling Peng; Meiyun Lv; Mengping Guo (Zeitschrift für Kristallographie - New Crystal Structures)
C14H10O4Se2, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 6.6836(11) Å, b = 8.9933(11) Å, c = 11.5062(19) Å, α = 77.128(12)°, β = 87.684(14)°, γ = 89.975(12)°, V = 673.65(18) Å3, Z = 2, R gt(F) = 0.0564, wR ref(F 2) = 0.1512, T = 293 K.